The effects of velocity-based versus percentage-based resistance training on athletic performances in sport-collegiate female basketball players - Zhang, Mingyang; Liang, Xingyue; Huang, Weifeng; Ding, Shicong; Li, Guoxing; Zhang, Wei; Li, Chao; Zhou, Yanfeng; Sun, Jian; Li, Duanying (Frontiers in Physiology, 2023)
To compare the effects of velocity-based (VBRT) and percentage-based resistance training (PBRT) on strength gains (one-repetition-maximum, 1RM), power adaptation, body composition and athletic performance in Sport-College female basketball players during 6 weeks of resistance-training. Fifteen participants were assigned to the VBRT (n=8) or PBRT (n=7) groups. Under linear periodization (65-95%1RM), the VBRT group’s loads were determined through the sessional corresponding target velocity and velocity loss, as opposed to %1RM in PBRT. Training loads data was continuously recorded, and body composition, 1RM, countermovement-jump (CMJ), squat-jump (SJ), eccentric-utilization-ratio (EUR), height and reactive-strength-index of drop-jump (DJ, DJ-RSI), plyometric-push-up (PPU), 505 change-of-direction (COD), 10-、20-m sprint (T-10、T-20), 17×15m drill-lines (17-drill), Hexagon agility, and functional movement screen (FMS) were measured in baseline (T0) and post-training (T2). A mid-term (T1) assessment was included to investigate the short-term effects of both methods and the fluctuation of personalized 1RM. No baseline differences were observed between-groups (p>0.05). VBRT and PBRT achieved similar strength gains for back squat (22.8% vs 19.6%) and bench press (11.2% vs 7.9%), but VBRT showed likely to very likely favorable improvements in CMJ (significant “group × time”，p=0.04), SJ, EUR, DJ-RSI, Hexagon and COD among sports function parameters. The VBRT showed likely to very likely improvements in 17-drill and DJ, while the PBRT showed unclear effects. The lifted weight of the VBRT method was higher than load prescription of the PBRT (p<0.05) for the same subjects while fewer repetitions (p<0.05). No inter-group differences at baseline to post-training was observed for FMS assessment (p>0.05). Compared with fixed-load PBRT, VBRT translated more into power output and athletic performance despite similar maximal strength gains. VBRT can be regarded as a more functional resistance-training with higher power and intensity adaptation.